The prognostic value of whole blood SOX2, NANOG and OCT4 mRNA expression in advanced small-cell lung cancer - Sodja, Eva (Radiology and oncology (Ljubljana), 2016)
The data on expression and clinical impact of cancer stem cell markers SOX2, NANOG and OCT4 in lung cancer is still lacking. The aim of our study was to compare SOX2, NANOG and OCT4 mRNA expression levels in whole blood between advanced small-cell lung cancer (SCLC) patients and healthy controls, and to correlate mRNA expression with progression-free survival (PFS) after first-line chemotherapy and overall survival (OS) in advanced SCLC patients. Patients and methods. 50 advanced SCLC patients treated with standard chemotherapy and followed at University Clinic Golnik, Slovenia, between 2009 and 2013 were prospectively included. SOX2, NANOG and OCT4 mRNA expression levels were determined using TaqMan qPCR in whole blood collected prior to chemotherapy. Whole blood of 34 matched healthy individuals with no cancerous disease was also tested. Results. SOX2 mRNA expression was significantly higher in whole blood of SCLC patients compared to healthy controls (p = 0.006). Significant correlation between SOX2 mRNA expression levels and the number of distant metastatic sites was established (p = 0.027). In survival analysis, patients with high SOX2 expression had shorter OS (p = 0.017) and PFS (p = 0.046). In multivariate Cox analysis, an independent value of high SOX2 expression for shorter OS (p = 0.002), but not PFS was confirmed. No significant differences were observed for NANOG or OCT4 expression levels when comparing SCLC patients and healthy controls neither when analysing survival outcomes in SCLC patients. Conclusions. SOX2 mRNA expression in whole blood might be a promising non-invasive marker for molecular screening of SCLC and important prognostic marker in advanced chemotherapy-treated SCLC patients, altogether indicating important role of cancer stem-like cell (CSC) regulators in cancer spread. Further evaluation of SOX2 as a possible screening/prognostic marker and a therapeutic target of SCLC is warranted.
Keywords: cancer stem cell markers; drobnocelični rak; napovedni dejavniki; pljuča; prognosis; rak (medicina); small-cell lung cancer; tumorski označevalci